The cytosolic isoform of glutaredoxin 2 promotes cell migration and invasion - Gellert, Manuela; Richter, Erik; Mostertz, Jörg; Kantz, Liane; Masur, Kai; Hanschmann, Eva-Maria; Ribback, Silvia; Kroeger, Nils; Schaeffeler, Elke; Winter, Stefan; Hochgräfe, Falko; Schwab, Matthias; et al. (Biochimica et biophysica acta. General subjects, 2020)
Cytosolic glutaredoxin 2 (Grx2c) controls axonal outgrowth and is specifically induced in many cancer cell lines. We thus hypothesized that Grx2c promotes cell motility and invasiveness. We characterized the impact of Grx2c expression in cell culture models. We combined stable isotope labeling, phosphopeptide enrichment, and high-accuracy mass spectrometry to characterize the underlying mechanisms. The most prominent associations were found with actin dynamics, cellular adhesion, and receptor-mediated signal transduction, processes that are crucial for cell motility. For instance, collapsin response mediator protein 2, a protein involved in the regulation of cytoskeletal dynamics, is regulated by Grx2c through a redox switch that controls the phosphorylation state of the protein as well. Cell lines expressing Grx2c showed dramatic alterations in morphology. These cells migrated two-fold faster and gained the ability to infiltrate a collagen matrix. The expression of Grx2c promotes cell migration, and may negatively correlate with cancer-specific survival. Our results imply critical roles of Grx2c in cytoskeletal dynamics, cell adhesion, and cancer cell invasiveness. [Display omitted] •Grx2c induces cell motility and invasiveness through redox regulation of proteins.•Redox signaling profoundly affects phosphorylation signaling.•Grx2c may be relevant in the development and progression of cancer.